2016
DOI: 10.1080/01419870.2016.1139155
|View full text |Cite
|
Sign up to set email alerts
|

Kazakh perspective on China, the Chinese, and Chinese migration

Abstract: Discourse analysis of different languages of newspapers in Kazakhstan reveals that Kazakhstanis' views toward China and the Chinese are divided. The official discourse in both state-sponsored Russian and Kazakh newspapers is in accordance with the country's policy toward further engagement with their rising Chinese neighbor.However, negative stereotypes of China and the Chinese, as well as sinophobia, are pervasive in private Kazakh language newspapers. Private Russian newspapers have a more nuanced view towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 19 publications
0
22
0
1
Order By: Relevance
“…As it was pointed out, CMNEs often lack independence in making investment decisions and particularly when it comes to engaging in corporate social responsibility projects. Another challenge for CMNEs that was not explored in this study is rising anti‐globalization sentiments and Sinophobia, which was reported particularly in the context of Central Asia (Burkhanov & Chen, ) amongst other cases. Future research could explore how perceptions of China in various locations could affect host government policies and CMNE strategies.…”
Section: Discussionmentioning
confidence: 97%
“…As it was pointed out, CMNEs often lack independence in making investment decisions and particularly when it comes to engaging in corporate social responsibility projects. Another challenge for CMNEs that was not explored in this study is rising anti‐globalization sentiments and Sinophobia, which was reported particularly in the context of Central Asia (Burkhanov & Chen, ) amongst other cases. Future research could explore how perceptions of China in various locations could affect host government policies and CMNE strategies.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, there is some apprehension that China's BRI is a 'geopolitical and diplomatic strategy that will ultimately constrain the policy choices of receiving countries' (Summers, 2016(Summers, , p. 1628. These widespread concerns in Kazakh communities have been reinforced by the growing numbers of Chinese working on railway and port construction projects which have led to complaints of them taking away local jobs (Burkhanov & Chen, 2016).…”
Section: Future Tourism and Brand Image Constructsmentioning
confidence: 99%
“…For instance, intellectuals such as Murat Auezov who was the Kazakh ambassador in Beijing usually asserts openly anti-Chinese statements in Kazakh-language media, evoking images of Chinese people as a peril or a natural disaster etc (Burkhanov and Chen 2016;Sadovskaya 2007;Syroezhkin 2009; Laurelle and Peyrouse 2012). In addition, Kazakhstani film industry has taken a keen interest in historical films, which depict the legendary past of the Kazakh nomads (e.g., The Nomad, Myn Bola) (Isaacs 2015).…”
Section: China In Kazakhstan's National Narrativementioning
confidence: 99%
“…Having said this, it is vital to note that the anti-Chinese sentiment from media and films to Kazakhstan's national narrative is rather minimal and mostly limited to a fraction of the Kazakh-language societal discourse. 1 Overall, Kazakhstan's national narrative is made by the president and his inner circle of advisors, promoting the concept of religious tolerance, multi-nationality and multi-culturalism, openness for investments and the willingness for cooperation with any multinational organisation (e.g., Shanghai Cooperation Organisation, European Union, Organisation for Economic Cooperation and Development) (Darden 2009: 207-221;Yemelianova, 2014;Burkhanov and Chen 2016). That said, Kazakhstani national elites are pretty much interested in the present and into business-making.…”
Section: China In Kazakhstan's National Narrativementioning
confidence: 99%